Impaired Emotional Mirroring in Parkinson’s Disease—A Study on Brain Activation during Processing of Facial Expressions - Pohl, Anna; Anders, Silke; Chen, Hong; Patel, Harshal Jayeshkumar; Heller, Julia; Reetz, Kathrin; Mathiak, Klaus; Binkofski, Ferdinand (Frontiers in Neurology, 2017)
Background: Affective dysfunctions are common in patients with Parkinson’s disease but the underlying neurobiological deviations have rarely been examined. Parkinson’s disease is characterized by a loss of dopamine neurons in the substantia nigra resulting in impairment of motor and non-motor basal ganglia-cortical loops. Concerning emotional deficits, some studies provide evidence for altered brain processing in limbic- and lateral-orbitofrontal gating loops. In a second line of evidence, human premotor and inferior parietal homologues of mirror neuron areas were involved in processing and understanding of emotional facial expressions. We examined deviations in brain activation during processing of facial expressions in patients and related these to emotion recognition accuracy. Methods: 13 patients and 13 healthy controls underwent an emotion recognition task and a functional magnetic resonance imaging (fMRI) measurement. In the Emotion Hexagon test participants were presented with blends of two emotions and had to indicate, which emotion best described the presented picture. Blended pictures with three levels of difficulty were included. During fMRI scanning, participants observed video clips depicting emotional, non-emotional and neutral facial expressions or were asked to produces these facial expressions themselves. Results: Patients performed slightly worse in the emotion recognition task, but only when judging the most ambiguous facial expressions. Both groups activated inferior frontal and anterior inferior parietal homologues of mirror neuron areas during observation and execution of the emotional facial expressions. During observation, responses in the pars opercularis of the right inferior frontal gyrus, in the bilateral inferior parietal lobule and in the bilateral supplementary motor cortex were decreased in patients. Furthermore, in patients activation of the right anterior inferior parietal lobule was positively related to accuracy in the emotion recognition task. Conclusion: Our data provide evidence for a contribution of human homologues of monkey mirror areas to the emotion recognition deficit in Parkinson’s disease.